Sequence similarity between HLA-DR1 and DR4 subtypes associated with rheumatoid arthritis and proteus/serratia membrane haemolysins. Issue 11 (November 1992) - Ebringer, A; Cunningham, P; Ahmadi, K; Wrigglesworth, J; Hosseini, R; Wilson, C
Abstract : Rheumatoid arthritis (RA) is found more often in subjects carrying the HLA-DR1 antigen and some subtypes of the HLA-DR4 antigen than in those without these antigens. Analysis of probes specific for HLA-DR4 has shown that amino acids encoding positions 69-74 (EQRRAA) of the beta chain indicates susceptibility to RA. A hexamer sequence of proteus haemolysin spanning residues 32-37 (ESRRAL) has been identified which resembles biochemically, and discriminates by charge, between HLA types associated with RA (DR1, Dw4, Dw14, Dw15), and those not linked with the disease (Dw10, Dw13).